Layanan Konseling Cognitive Behavior Therapy (CBT) Dalam Menangani Permasalahan Psikologis Anak Broken Home: A Systematic Literature Review - Siti Rahayu Fadilah; Akhmad Fajar Prasetya (STKIP Subang, 2026)
Children with broken homes often experience psychological problems that have a significant impact on various aspects of their emotional and social development. One effective intervention to address this problem is Cognivite Behavior Therapy by changing negative mindsets, perceptions, and behaviors and helping individuals identify and correct negative automatic thoughts. This study aims to analyze, evaluate and integrate the latest findings related to the role of Cognitive Behavior Therapy through the systematic literature review of the PRISMA method. Literature search was carried out using a search engine in the form of Google Schoolar, articles were downloaded and reviewed using inclusion and exclusion criteria, followed by a synthesis analysis process. The results of the study show that Cognivite Behavior Therapy is effective in helping children with broken homes overcome various psychological problems, such as excessive anxiety and sadness, low self-esteem and identity crisis. In addition, Cognitive Behavior Therapy equips broken home children with coping strategies to practice independence in overcoming their problems. In several studies, Cognitive Behavior Therapy has also been successful in improving learning motivation, social relationships and interpersonal communication